Unveiling the Forgotten Aspect of Good Deeds: A Comparative Study of Muslims Thoughts - Mohd Rosmizi Abd Rahman; Mohamed Mihlar Abdul Muthaliff; Marina Munira Abdul Mutalib; Rezki Perdani Sawai; Roslizawati Mohd Ramly (Human Resource Management Academic Research Society, 2024)
Indexed by ERA